A novel 4-sensor fast-response aerodynamic probe for non-isotropic turbulence measurement in turbomachinery flows. (17th May 2018) - Chasoglou, Alexandros C.; Mansour, Michel; Kalfas, Anestis I.; Abhari, Reza S.
Abstract: In modern computational studies for turbomachinery applications, time, length scales and isotropy of turbulent structures are important for representative modelling. To this end, experimental data are essential to validate the numerical tools. The current article presents the development and application of a newly designed 4-sensor Fast Response Aerodynamic Probe (FRAP-4S) enabling time-resolved measurement of the three-dimensional unsteady flow velocity vector in turbomachines. The miniature multi-sensor probe demonstrates a 4 mm probe-tip. In the first part of this article the design, manufacturing and calibration results of the FRAP-4S are presented in detail. To assess the newly developed probe accuracy, comparison against traditional instrumentation developed at the Laboratory for Energy Conversion is also provided. In the second part of this work, measurements are performed at the rotor exit of a one-and-a-half stage, unshrouded and highly-loaded axial turbine configuration. The results showed increased level of unsteadiness and turbulence levels with peak-to-peak fluctuation from 5 to 35%. More importantly, in some regions stream-wise unsteadiness was found to be ten times higher, compared to the cross-wise components, an indication of the high degree of anisotropy.